Genetic diversity and natural selection of the rhoptry-associated protein 1 (RAP-1) of recent Plasmodium knowlesi clinical isolates from Malaysia / Mira Syahfriena Amir Rawa - Mira Syahfriena , Amir Rawa (2016)

(untitled)
The Plasmodium rhoptry-associated protein 1 (RAP-1) plays a role in the formation of the parasitophorous vacuole following the parasite‟s invasion of red blood cells. Although there is some evidence that the protein is recognized by the host‟s immune system, a study of Plasmodium falciparum RAP-1 suggests that it is not under immune pressure. A previous study on five old P. knowlesi strains (1953-1962) suggested that RAP-1 has limited genetic polymorphism and might be under negative selection. In the present study, 30 recent P. knowlesi isolates were studied to obtain a better insight into the polymorphism and natural selection of P. knowlesi RAP-1. Blood samples from 30 knowlesi malaria patients were used. These samples were collected between 2010 and 2014. The P. knowlesi RAP-1 gene, which contains two exons, was amplified by PCR, cloned into Escherichia coli and sequenced. Genetic diversity and phylogenetic analyses were performed using MEGA6 and DnaSP ver. 5.10.00 programs. Thirty P. knowlesi RAP-1 sequences were obtained. The nucleotide diversity (π) of exons 1, 2 and the total coding region (0.00915, 0.01353 and 0.01298, respectively) were higher than those of the old strains. Further analysis revealed a lower rate of non-synonymous (dN) than synonymous (dS) mutations, suggesting negative (purifying) selection of P. knowlesi RAP-1. Tajima‟s D test and Fu and Li‟s D test values were not significant. At the amino acid level, 22 haplotypes were established with haplotype H7 having the highest frequency (7/34, 20.5%). In the phylogenetic analysis, two distinct haplotype groups were observed. The first group contained the majority of the haplotypes, whereas the second had fewer haplotypes. The present study found higher genetic polymorphism in the P. knowlesi RAP-1 gene than the polymorphism level reported in the previous study. This observation may stem from the difference in sample size between the present (n=30) and the previous (n=5) study. Synonymous and iv nonsynonymous mutation analysis indicated purifying (negative) selection of the gene. The separation of P. knowlesi RAP-1 haplotypes into two groups provides further evidence on the postulation of two distinct P. knowlesi types or lineages.